Evaluation of the degree of competitiveness of five companies of the dary sector in Sincelejo, Colombia (2014)
The dairy agribusiness is struggling in the middle of competitive forces that affect their strategy and survival. Hence, they have to build sustainable competitive advantages to foster growth and development. Doing so, companies must create a baseline of its present and then, define the corresponding strategies. This document evaluates de degree of competitiveness of five dairy companies in Sincelejo, Colombia through a case study that applied a questionnaire inspired in the functional areas of the enterprise. The questionnaire inquired on elements in the following categories: production, marketing, finances, administration and human talent. We conclude that the level of competitiveness of the analyzed companies is low where the components of production, administration and human talent, have a better performance compared to marketing and finance.